YOUNG TEENAGERS PROVIDING THEIR OWN SURGICAL CONSENTS: An Ethical-Legal Dilemma For Perioperative Registered Nurses - Kuz, Kelly (Operating Room Nurses Association of Canada Journal, 2006)
During the delivery of health care, ethical-legal problems are not uncommon and can be defined as situations that have potential legal consequences when equally compelling ethical reasons for and against a particular course of action are recognized and a decision must be made.1 Ethical-legal repercussions may occur when obtaining surgical consent from a younger teenager (defined as dependant and/or under 18 years of age). An ethical-legal dilemma arising from the case of a 14- year-old, run away girl, who had signed her own surgical consent for a cholecystectomy is analyzed. The concept of consent is discussed and related to an actual case study. The elements of a valid informed consent are identified, discussed and related to the case study. Using the MORAL model for ethical decision-making2 the ethical implications of this case are analysed. Possible legal repercussions are addressed and a risk management strategy (suggested policy and documentation protocols for the consent process) is proposed and evaluated.